Aging-resistant holographic polymer dispersed liquid crystal material, grating device and preparation method thereof
By adding monomers with different functionalities into the holographic polymer dispersed liquid crystal material, the efficiency of the polymerization reaction between monomers is improved, the problem of material performance degradation in high temperature environments is solved, and higher thermal stability and longer life are achieved. service life.
Patent Information
- Application Number
- CN202411388109.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Holographic polymer dispersed liquid crystal materials are prone to problems such as material quality reduction and polymer matrix degradation in high temperature environments, resulting in a gradual reduction in overall performance and a shortened service life.
By adding the first monomer, the second monomer and the third monomer with different functionalities, the ratio is adjusted to improve the efficiency of the polymerization reaction between the monomers and enhance the thermal stability of the material. Specifically, 2-(p-cumyl-phenoxy)-ethyl acrylate, dicyclopentenyl ethoxymethacrylate, and dicyclopentenyl acrylate are selected as the first monomer, and tricyclodecyl Alkanedimethanol dimethacrylate, bistrimethylolpropane tetraacrylate as the second monomer, and tris(2-hydroxyethyl)isocyanurate triacrylate as the third monomer.
The thermal stability of the holographic polymer dispersed liquid crystal material is improved, the service life of the grating device is extended, and the production cost is reduced, while the overall performance and diffraction efficiency of the material are enhanced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of holographic projection display, and more specifically, to an ageing-resistant holographic polymer dispersed liquid crystal material, a grating device and a preparation method thereof. Background Art
[0002] Nowadays, with the continuous updating and iteration of market demand and technology, various holographic technologies are gradually applied to various occasions in people's lives. Among them, holographic display technology is the most intuitive application of holographic technology. With the continuous development of holographic technology, holographic display technology is also gradually being integrated into various fields such as reflective flat-panel displays, teaching displays, medical diagnosis and treatment, and military technology.
[0003] As one of the fastest-growing, most widely used, and most closely related optoelectronic materials since the last century, liquid crystal is still widely used in the display of various electronic devices. Thanks to the tunable nature of liquid crystal materials, the arrangement direction of liquid crystal molecules can be controlled by applying external fields such as electric fields, magnetic fields, and heat, thereby realizing different functions of the device, greatly improving the multi-dimensional flexible controllability of devices in the current electronics industry. Among them, polymer dispersed liquid crystal (PDLC) is an optoelectronic functional device based on liquid crystal / polymer materials. It mainly transforms the mixture of liquid crystal and prepolymer into liquid crystal droplets dispersed in the polymer substrate by photopolymerization or thermal polymerization to cause phase separation, and then uses the electrical control characteristics of liquid crystal to control the orientation of liquid crystal molecules by applying an external voltage, thereby changing the refractive index of liquid crystal to match or mismatch the refractive index of the polymer, resulting in the polymer dispersed liquid crystal film switching between light transmission or light scattering under the action of an electric field.
[0004] Holographic Polymer Dispersed Liquid Crystal (H-PDLC) is a combination of holographic technology and polymer dispersed liquid crystal. It is a composite material with holographic display function and a certain ordered arrangement structure system. H-PDLC is formed by periodic arrangement of polymer-rich phase and liquid crystal-rich phase. It is formed by polymerization-induced phase separation under coherent laser. Specifically, a laser beam is divided into two coherent beams of equal light intensity, and then converged to obtain an interference light field with a sinusoidal distribution of light intensity, and light intensity modulation is generated in the interference area; in the interference bright fringe area (i.e., coherent bright area), the photoinitiator system absorbs light energy, generates active free radicals, and initiates monomer polymerization. The polymerization reaction causes the chemical potential of the system to change, causing the monomer to diffuse from the coherent dark area to the coherent bright area, and the liquid crystal diffuses to the coherent dark area, and finally produces a holographic grating structure composed of alternating polymer-rich phases and liquid crystal-rich phases. Holographic polymer dispersed liquid crystal materials have a variety of functions and have been widely used in electro-optical response photonic crystals, color 3D holographic image storage, distributed feedback lasers, sensors and other fields. In addition, due to its excellent electro-optical response characteristics and high refractive index modulation, holographic polymer dispersed liquid crystal materials also show great application potential in the field of augmented reality.
[0005] However, in practical applications, holographic polymer dispersed liquid crystal materials, as a composite material, usually encounter problems such as reduced material quality and polymer matrix degradation in high temperature environments. As the high temperature exposure time increases, the comprehensive performance of the composite material gradually decreases and the service life is greatly reduced. Therefore, in order for holographic polymer dispersed liquid crystal materials to maintain stable performance for a long time, it is necessary to improve the thermal stability of the material. Summary of the invention
[0006] The present invention aims to overcome at least one defect of the above-mentioned prior art, and provides an aging-resistant holographic polymer dispersed liquid crystal material, a grating device and a preparation method thereof, thereby improving the material thermal stability of the holographic polymer dispersed liquid crystal material, thereby improving the comprehensive performance and service life of the holographic polymer dispersed liquid crystal material and the grating device prepared therefrom.
[0007] The technical solution adopted by the present invention is first to provide an anti-aging holographic polymer dispersed liquid crystal material, which comprises, by mass percentage:
[0008] Solvent: 5%-15%,
[0009] LCD: 35-55%,
[0010] Photoinitiator: 0.5-2%,
[0011] Co-initiator: 0.5-10%,
[0012] First monomer: 5-40%,
[0013] Second monomer: 5-40%,
[0014] The third monomer: 1-10%;
[0015] The first monomer is selected from one or more of 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate, dicyclopentenyl ethoxylated methacrylate and dicyclopentenyl acrylate;
[0016] The second monomer is selected from one or more of tricyclodecane dimethanol dimethacrylate, tricyclodecane dimethanol diacrylate and dioxane hexanediol diacrylate;
[0017] The third monomer is one or more of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, ditrimethylolpropane tetraacrylate and 2 mol caprolactone-modified dipentaerythritol hexaacrylate.
[0018] In the present technical solution, by adding a first monomer, a second monomer and a third monomer with different functionalities, the efficiency of the polymerization reaction between the monomers can be improved by adjusting the ratio of the monomers with different functionalities added, which not only makes the holographic polymer dispersed liquid crystal material more suitable for exposure processing, but also allows the monomers to move effectively in space by adding only a small amount of solvent for dilution, while improving the degree of polymerization between the monomers and the diffraction efficiency and function of the prepared holographic grating device. Specifically, the first monomer is a monofunctional monomer selected from one or more of 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate, dicyclopentenyl ethoxylated methacrylate and dicyclopentenyl acrylate; the second monomer is a difunctional monomer selected from one or more of tricyclodecane dimethanol dimethacrylate, tricyclodecane dimethanol diacrylate and dioxane hexanedioic acid diacrylate; the third monomer is a multifunctional monomer, specifically, selected from one or more of tri(2-hydroxyethyl) isocyanuric acid triacrylate or pentaerythritol triacrylate having a trifunctional group, ditrimethylolpropane tetraacrylate having a tetrafunctional group, and 2 mol caprolactone-modified dipentaerythritol hexaacrylate having a pentafunctional group; the thermal stability of the holographic polymer dispersed liquid crystal material is improved by the combined use of the three types of polymer monomers, so that the holographic volume grating device prepared with the holographic polymer dispersed liquid crystal material has better comprehensive performance and service life. At the same time, the polymer monomers contained in the holographic polymer dispersed liquid crystal material have a variety of choices, and the sources of the raw materials are wide and easy to obtain. While ensuring the function of the holographic grating device, it improves the production convenience and reduces the production cost.
[0019] Furthermore, the photoinitiator is selected from one or more of rose bengal, camphorquinone, methylene blue and ethyl eosin.
[0020] Furthermore, the co-initiator is selected from one or more of N,N-dimethylaniline, Lencolo 5031 and N-phenylglycine.
[0021] Furthermore, the liquid crystal is selected from one or more of E7, E63, P0616A, BL038 and TEB30A.
[0022] Furthermore, the solvent is selected from one or more of cyclohexane, dichloromethane, dimethylformamide and N-ethylpyrrolidone.
[0023] Another object of the present invention is to provide a method for preparing a holographic polymer dispersed liquid crystal grating device. The preparation method has a simple process, does not require post-curing, has low production cost, and high production efficiency. The preparation method specifically comprises the following steps:
[0024] The aging-resistant holographic polymer dispersed liquid crystal material provided in the technical solution is mixed and poured into a liquid crystal box, placed still in a dark room, and then subjected to interference exposure under the interference light field of a double-beam light source.
[0025] Optionally, the interference exposure time is 1-5 min, and the irradiation power is 5-7 mW / cm 2 ; The angle between the dual-beam light sources is 40°-60°.
[0026] Preferably, a double beam angle of 45° and an optical power of 6 mW / cm 2 The material was exposed to a dual-beam light source for 3 min to prepare a holographic polymer dispersed liquid crystal grating device.
[0027] Optionally, the thickness of the liquid crystal box is 5 μm-10 μm.
[0028] Preferably, the holographic polymer dispersed liquid crystal material is mixed and filled into a liquid crystal box with a thickness of 5 μm under vacuum atmosphere, and is left to stand in a dark room for 1 hour.
[0029] Another object of the present invention is to provide a holographic polymer dispersed liquid crystal grating device, which is prepared by the preparation method provided by the technical solution.
[0030] Compared with the prior art, the beneficial effects of the present invention are as follows: first, by adding a first monomer, a second monomer and a third monomer with different functionalities, the efficiency of the polymerization reaction between the monomers can be improved by adjusting the ratio of the monomers with different functionalities added, which not only makes the holographic polymer dispersed liquid crystal material more suitable for exposure processing, but also allows the monomers to move effectively in space by adding only a small amount of solvent for dilution, while improving the polymerization degree between the monomers and the diffraction efficiency and function of the prepared holographic grating device.
[0031] Secondly, through the creative selection and combined use of three types of polymer monomers, namely, single-functional monomers, bifunctional monomers and multifunctional monomers, the overall thermal stability of the holographic polymer dispersed liquid crystal material is improved, so that the holographic volume grating device prepared with the holographic polymer dispersed liquid crystal material has better comprehensive performance and service life; at the same time, the polymer monomers contained in the holographic polymer dispersed liquid crystal material are diverse in choice, and the raw materials thereof are widely available and easy to obtain, which improves the production convenience and reduces the production cost while ensuring the function of the holographic volume grating device. DETAILED DESCRIPTION
[0032] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0034] The present invention is further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following contents (if the specific experimental conditions are not specified in the examples, they are usually carried out according to conventional conditions or according to the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples can be obtained from commercial channels unless otherwise specified). In the following examples, 2 moles of caprolactone-modified dipentaerythritol hexaacrylate is EM2692 produced by Changxing Materials Industry Co., Ltd.
[0035] Example 1
[0036] This embodiment provides an aging-resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0037] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0038] Methylene blue 1.5%, N-phenylglycine 5%, TEB30A 35%, 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate 16%, dicyclopentenyl ethoxylated methacrylate 12%, tricyclodecane dimethanol dimethacrylate 17%, 2 mol caprolactone modified dipentaerythritol hexaacrylate 6%, dimethylformamide 3%, N-ethylpyrrolidone 4.5%.
[0039] (2) Preparation of holographic polymer dispersed liquid crystal materials
[0040] The weighed raw materials are mixed evenly to obtain an ageing-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0041] (3) Preparation of holographic polymer dispersed liquid crystal grating devices
[0042] The above-mentioned aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions, and allowed to stand in a dark room for 1 hour.
[0043] Then, a double beam with an angle of 45° and an optical power of 6 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0044] (4) Diffraction efficiency test and haze test
[0045] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0046] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0047] (5) Aging test
[0048] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0049] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0050] Example 2
[0051] This embodiment provides an aging-resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0052] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0053] Rose Red 1%, Lencolo 5031 2.5%, E7 38%, dicyclopentenyl acrylate 15%, 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate 14%, 15% dioxanediol diacrylate, 8% ditrimethylolpropane tetraacrylate, 6.5% dimethylformamide.
[0054] (2) Preparation of holographic polymer dispersed liquid crystal materials
[0055] The weighed raw materials are mixed evenly to obtain an aging-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0056] (3) Preparation of holographic polymer dispersed liquid crystal grating devices
[0057] The above-mentioned aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions, and allowed to stand in a dark room for 1 hour.
[0058] Then, a double beam with an angle of 45° and an optical power of 6 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0059] (4) Diffraction efficiency test and haze test
[0060] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0061] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0062] (5) Aging test
[0063] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0064] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0065] Example 3
[0066] This embodiment provides an aging-resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0067] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0068] Ethyl eosin 2%, N,N-dimethylaniline 3%, E63 37%, dicyclopentenyl acrylate 15%, tricyclodecane dimethanol diacrylate 10%, 15% dioxane diol diacrylate, 8% tris(2-hydroxyethyl)isocyanuric acid triacrylate, 5% cyclohexane, 5% N-ethylpyrrolidone.
[0069] (2) Preparation of holographic polymer dispersed liquid crystal materials
[0070] The weighed raw materials are mixed evenly to obtain an ageing-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0071] (3) Preparation of holographic polymer dispersed liquid crystal grating devices
[0072] The above-mentioned aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions, and allowed to stand in a dark room for 1 hour.
[0073] Then, a double beam with an angle of 45° and an optical power of 6 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0074] (4) Diffraction efficiency test and haze test
[0075] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0076] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0077] (5) Aging test
[0078] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0079] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0080] Example 4
[0081] This embodiment provides an aging-resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0082] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0083] Camphorquinone 0.5%, N, N-dimethylaniline 3%, P0616A 38%, dicyclopentenyl ethoxylated methacrylate 20%, tricyclodecane dimethanol dimethacrylate 14%, 10% hexadecane diol diacrylate, 7% pentaerythritol triacrylate, 5% dichloromethane, 2.5% cyclohexane.
[0084] (2) Preparation of holographic polymer dispersed liquid crystal materials
[0085] The weighed raw materials are mixed evenly to obtain an ageing-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0086] (3) Preparation of holographic polymer dispersed liquid crystal grating devices
[0087] The above-mentioned aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions, and allowed to stand in a dark room for 1 hour.
[0088] Then, a double beam with an angle of 45° and an optical power of 6 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0089] (4) Diffraction efficiency test and haze test
[0090] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0091] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0092] (5) Aging test
[0093] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0094] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0095] Example 5
[0096] This embodiment provides an aging-resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0097] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0098] Camphorquinone 1%, N-phenylglycine 3%, BL038 35%, 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate 25%, tricyclodecane dimethanol diacrylate 20%, tris(2-hydroxyethyl) isocyanuric acid triacrylate 5%, ditrimethylolpropane tetraacrylate 4%, dichloromethane 4%, dimethylformamide 3%.
[0099] (2) Preparation of holographic polymer dispersed liquid crystal materials
[0100] The weighed raw materials are mixed evenly to obtain an ageing-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0101] (3) Preparation of holographic polymer dispersed liquid crystal grating devices
[0102] The above-mentioned aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions, and allowed to stand in a dark room for 1 hour.
[0103] Then, a double beam with an angle of 45° and an optical power of 6 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0104] (4) Diffraction efficiency test and haze test
[0105] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0106] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0107] (5) Aging test
[0108] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0109] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0110] Comparative Example 1
[0111] This comparative example provides an aging-resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0112] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0113] Methylene blue 1.5%, N-phenylglycine 5%, TEB30A 35%, 2-carboxyethyl acrylate 15%, isooctyl acrylate 13%, tricyclodecane dimethanol dimethacrylate 17%, 2 mol caprolactone-modified dipentaerythritol hexaacrylate 6%, dimethylformamide 3%, N-ethylpyrrolidone 4.5%.
[0114] (2) Preparation of holographic polymer dispersed liquid crystal materials
[0115] The weighed raw materials are mixed evenly to obtain an ageing-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0116] (3) Preparation of holographic polymer dispersed liquid crystal grating devices
[0117] The above-mentioned aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions, and allowed to stand in a dark room for 1 hour.
[0118] Then, a double beam with an angle of 45° and an optical power of 6 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0119] (4) Diffraction efficiency test and haze test
[0120] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0121] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0122] (5) Aging test
[0123] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0124] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0125] Comparative Example 2
[0126] This comparative example provides an aging-resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0127] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0128] Rose Red 1%, Lencolo 5031 2.5%, E7 38%, dicyclopentenyl acrylate 15%, 2-dimethylpropyl diacrylate 14%, 2-methyl-1,3-propanediol diacrylate 15%, ditrimethylolpropane tetraacrylate 8%, dimethylformamide 6.5%.
[0129] (2) Preparation of holographic polymer dispersed liquid crystal materials
[0130] The weighed raw materials are mixed evenly to obtain an ageing-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0131] (3) Preparation of holographic polymer dispersed liquid crystal grating devices
[0132] The above-mentioned aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions, and allowed to stand in a dark room for 1 hour.
[0133] Then, a double beam with an angle of 45° and an optical power of 6 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0134] (4) Diffraction efficiency test and haze test
[0135] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0136] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0137] (5) Aging test
[0138] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0139] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0140] Comparative Example 3
[0141] This comparative example provides an aging-resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0142] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0143] Ethyl eosin 2%, N,N-dimethylaniline 3%, E63 37%, 2-carboxyethyl acrylate 15%, 2-methyl-1,3-propanediol diacrylate 10%, isooctyl acrylate 15%, tris(2-hydroxyethyl)isocyanurate triacrylate 8%, cyclohexane 5%, N-ethylpyrrolidone 5%.
[0144] (2) Preparation of holographic polymer dispersed liquid crystal materials
[0145] The weighed raw materials are mixed evenly to obtain an ageing-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0146] (3) Preparation of holographic polymer dispersed liquid crystal grating devices
[0147] The above-mentioned aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions, and allowed to stand in a dark room for 1 hour.
[0148] Then, a double beam with an angle of 45° and an optical power of 6 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0149] (4) Diffraction efficiency test and haze test
[0150] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0151] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0152] (5) Aging test
[0153] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0154] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0155] Comparative Example 4
[0156] This comparative example provides an aging-resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0157] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0158] Methylene blue 1.5%, N-phenylglycine 5%, TEB30A 35%, 2-carboxyethyl acrylate 15%, 2-dimethylpropyl diacrylate 13%, 2-methyl-1,3-propanediol diacrylate 17%, 2 mol caprolactone-modified dipentaerythritol hexaacrylate 6%, dimethylformamide 3%, N-ethylpyrrolidone 4.5%.
[0159] (2) Preparation of holographic polymer dispersed liquid crystal materials
[0160] The weighed raw materials are mixed evenly to obtain an ageing-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0161] (3) Preparation of holographic polymer dispersed liquid crystal grating devices:
[0162] The above-mentioned aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions, and allowed to stand in a dark room for 1 hour.
[0163] Then, a double beam with an angle of 45° and an optical power of 6 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0164] (4) Diffraction efficiency test and haze test
[0165] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0166] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0167] (5) Aging test
[0168] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0169] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0170] In Examples 1 to 5, the holographic polymer dispersed liquid crystal material is set to be selected and combined from the first monomer, the second monomer and the third monomer provided in the technical solution, wherein the first monomer is selected from one or more of 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate, dicyclopentenyl ethoxylated methacrylate and dicyclopentenyl acrylate; the second monomer is selected from one or more of tricyclodecane dimethanol dimethacrylate, tricyclodecane dimethanol diacrylate and dioxane hexaglycol diacrylate; the third monomer is selected from one or more of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, ditrimethylolpropane tetraacrylate and 2 mol caprolactone modified dipentaerythritol hexaacrylate. In Comparative Examples 1 to 4, at least one type of polymer monomer selected from the first monomer, the second monomer or the third monomer in the holographic polymer dispersed liquid crystal material formed is selected from other monomers that are not within the selection range of the first monomer, the second monomer and the third monomer provided in the technical solution.
[0171] The results of the diffraction efficiency change rate and haze change rate of the 9 holographic polymer dispersed liquid crystal materials and the grating devices prepared therefrom in Comprehensive Examples 1 to 5 and Comparative Examples 1 to 4 after aging tests are shown in the following table:
[0172]
[0173] By comparing the embodiments and the comparative examples, it can be found that the obtained diffraction efficiency change rate and haze change rate results after the aging test show that when the first monomer, the second monomer and the third monomer contained in the holographic polymer dispersed liquid crystal material are selected and combined accordingly according to the polymer monomer range provided in the present invention, the absolute values of the diffraction efficiency change rate and the haze change rate of the prepared holographic polymer dispersed liquid crystal grating device after the aging test are greatly reduced, indicating that the holographic polymer dispersed liquid crystal material obtained in the embodiment and the grating device prepared therefrom have a smaller change amount of the device under high-temperature aging conditions, and its comprehensive performance is more stable, that is, it has better thermal stability, so that the prepared holographic polymer dispersed liquid crystal grating device has better comprehensive performance and longer service life, and is also suitable for a wider range of usage scenarios.
[0174] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. An ageing-resistant holographic polymer dispersed liquid crystal material, characterized in that: In terms of mass percentage, it includes: Solvent: 5%-15%, LCD: 35-55%, Photoinitiator: 0.5-2%, Co-initiator: 0.5-10%, First monomer: 5-40%, Second monomer: 5-40%, The third monomer: 1-10%; The first monomer is selected from one or more of 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate, dicyclopentenyl ethoxylated methacrylate and dicyclopentenyl acrylate; The second monomer is selected from one or more of tricyclodecane dimethanol dimethacrylate, tricyclodecane dimethanol diacrylate, and dioxane hexanedioic acid diacrylate; The third monomer is one or more of tris(2-hydroxyethyl)isocyanurate triacrylate, pentaerythritol triacrylate, ditrimethylolpropane tetraacrylate and 2 mol caprolactone-modified dipentaerythritol hexaacrylate.
2. The aging-resistant holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The photoinitiator is selected from one or more of rose bengal, camphorquinone, methylene blue and ethyl eosin.
3. The aging-resistant holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The co-initiator is selected from one or more of N,N-dimethylaniline, Lencolo 5031 and N-phenylglycine.
4. The aging-resistant holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The liquid crystal is selected from one or more of E7, E63, P0616A, BL038 and TEB30A.
5. The aging-resistant holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The solvent is selected from one or more of cyclohexane, dichloromethane, dimethylformamide and N-ethylpyrrolidone.
6. A method for preparing a holographic polymer dispersed liquid crystal grating device, characterized in that: The following steps are involved: The ageing-resistant holographic polymer dispersed liquid crystal material according to any one of claims 1 to 5 is mixed and poured into a liquid crystal box, placed still in a dark room, and then subjected to interference exposure under the interference light field of a double-beam light source.
7. The preparation method according to claim 6, characterized in that: The interference exposure time is 1-5 minutes, and the irradiation power is 5-7 mW / cm 2 ; and the angle between the dual-beam light sources is 40°-60°.
8. The preparation method according to claim 6, characterized in that: The thickness of the liquid crystal cell is 5-10 μm.
9. The preparation method according to claim 6, characterized in that: The holographic polymer dispersed liquid crystal material is mixed and filled into a liquid crystal box under a vacuum atmosphere, and allowed to stand in a dark room for 1 hour.
10. A holographic polymer dispersed liquid crystal grating device, characterized in that: Prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
PDLC (Polymer Dispersed Liquid Crystal) dimming material, dimming film and preparation method of dimming film
CN114672322A
Thermal-oxidative-aging-resistant holographic polymer dispersed liquid crystal composition, grating and preparation method
CN118421332A